The toxic benthic dinoflagellate Prorocentrum maculosum Faust is a synonym of Prorocentrum hoffmannianum Faust - Rodríguez, Francisco; Riobó, Pilar; Crespín, Guillermo D.; Hernández Daranas, Antonio; de Vera, Caterina R.; Norte, Manuel; Fernández, José J.; Fraga, Santiago (Harmful Algae, 2018)
Three strains of the toxic benthic dinoflagellate Prorocentrum hoffmannianum were isolated in the Canary Islands (north-east Atlantic Ocean, Spain). The identity of the strains was determined by phylogenetic analyses of partial LSU rDNA (D1-D2 regions) but their morphology based on SEM images corresponded to P. maculosum. Their toxin profiles were analyzed by liquid chromatography and high resolution mass spectrometry analysis (LC–HRMS) on cell extracts and culture media. Okadaic acid and three analogs were detected in all strains. Rather, in culture media the detected compounds were variable among strains, two of them being okadaic acid analogs not found on cell extracts. As a result, the taxonomy of the species was revised and P. maculosum is proposed as a junior synonym of P. hoffmannianum whose description is emended. Peer reviewed